Effect of Aerobic Exercise on Brain-derived Neurotrophic Factor (BDNF) Serum Level in Stroke Subjects with Cognitive Function Impairment - Vanydia Aisyah; Subagyo Subagyo; Imam Subadi (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Cognitive impairment is the most frequent complication of stroke. However, erobic exercise is considered to have potential effect in inhibiting the post-stroke cognitive degradation and increasing cognitive performance through neuroplasticity-influenced long term potentiation in hippocampus.Aim: To determine the effect of aerobic exercise on brain-derived neurotrophic factor (BDNF) serum level in stroke subjects with cognitive function impairment.Material and Methods: Experimental pre-post study on sub-acute stroke male and female, 12 subjects on each group. Intervention group given standard therapy and aerobic exercise using static cycle. Control group treated with standard therapy 30 minutes/session 3x/week, for 6 weeks. Parameter being evaluated was BDNF serum level.Result: No significant difference (p=0.21) in BDNF serum level in both control group (246.03±40.81 pg/ml) and intervention group (280.98±73.53 pg/ml) after treated with treatment. Although there was a significant increase of BDNF serum level in the intervention group (p<0.001) with pre-intervention mean value of 1.96±60.69 pg/ml and post-intervention mean value of 280.98±73.53 pg/ml. Similar to the intervention group, there was a significant increase in BDNF serum level (p<0,001) in control group, with pre-intervention mean value of 136.39±76.32 pg/ml and post-intervention mean value of 246.03±40.81 pg/ml.Conclusion: No significant difference in BDNF serum levels in intervention group after aerobic exercise program with a static cycle and standard therapy 3x/week for 6 weeks, when compared to the control group that only received standard therapy, although both control and intervention groups showed significant difference before and after the intervention.